Observations on the rhetorical device of feminisation in Ciceronian invective - Cairo, María Emilia (Ciceroniana On Line, 2024)
In Cicero’s invective speeches, his adversaries are usually represented as “non-Romans” — that is, as individuals not belonging to the community—through the deployment of different rhetorical devices that isolate them and exclude them from the res publica. One such device is feminization. The attribution of traits, behaviours, and ways of dressing and speaking identified as typical of women contribute to the negative characterization of Verres, Catiline, Clodius, Mark Antony and Gabinius, and to their exclusion from the Roman prototype postulated by Cicero, i.e., that of the civis, a male citizen, competent, and of legal age who participates in public life.